Habermas contra el hiperracionalismo: apuntes del debate Habermas-Luhmann a propósito del tópico marxista de la ideología - Sotomayor, Enrique (2014)
This paper presents a revision of the way in which Jürgen Habermas returns to the critical tradition of Marxism regarding the topic of ideology. After the characterization of Habermasian thinking regarding the progress of instrumental rationality (at the expense of communicative reason) it confronts the debate between Habermas and Niklas Luhmann within German Social Theory. Finally, the third section focuses on showing the differences regarding the conception of the place of law in society, based on the theoretical frameworks of Habermas and Luhmann.